Earth as Interface: Exploring chemical senses with Multisensory HCI Design for Environmental Health Communication - Neves, Paula Cristina Marques (2021)
As environmental problems intensify, the chemical senses -that is smell and taste, are the most relevantsenses to evidence them.As such, environmental exposure vectors that can reach human beings comprise air,food, soil and water[1].Within this context, understanding the link between environmental exposures andhealth[2]is crucial to make informed choices, protect the environment and adapt to new environmentalconditions[3].Smell and taste lead therefore to multi-sensorial experiences which convey multi-layered information aboutlocal and global events[4]. However, these senses are usually absent when those problems are represented indigital systems. The multisensory HCIdesign framework investigateschemical sense inclusion withdigital systems[5]. Ongoing efforts tackledigitalization of smell and taste for digital delivery, transmission or substitution [6]. Despite experimentsproved technological feasibility, its dissemination depends on relevant applicationdevelopment[7].This thesis aims to fillthose gaps by demonstratinghow chemical senses provide the means to link environment and health based on scientific andgeolocation narratives [8], [9],[10]. We present a Multisensory HCI design process which accomplished symbolicdisplaying smell and taste and led us to a new multi-sensorial interaction system presented herein. We describe the conceptualization, design and evaluation of Earthsensum, an exploratory case study project.Earthsensumoffered to 16 participants in the study, environmental smell and taste experiences about real geolocations to participants of the study. These experiences were represented digitally using mobilevirtual reality (MVR) and mobile augmented reality (MAR). Its technologies bridge the real and digital Worlds through digital representations where we can reproduce the multi-sensorial experiences. Our study findings showed that the purposed interaction system is intuitive and can lead not only to a betterunderstanding of smell and taste perception as also of environmental problems. Participants comprehensionabout the link between environmental exposures and health was successful and they would recommend thissystem as education tools. Our conceptual design approach was validated and further developments wereencouraged.In this thesis,we demonstratehow to applyMultisensory HCI methodology to design with chemical senses. Weconclude that the presented symbolic representation model of smell and taste allows communicatingtheseexperiences on digital platforms. Due to its context-dependency, MVR and MAR platforms are adequatetechnologies to be applied for this purpose.Future developments intend to explore further the conceptual approach. These developments are centredon the use of the system to induce hopefully behaviourchange. Thisthesisopens up new application possibilities of digital chemical sense communication,Multisensory HCI Design and environmental health communication.